2020
DOI: 10.1097/meg.0000000000001558
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and adherence to nucleos(t)ide analogues in chronic hepatitis B: a multicenter cohort study

Abstract: Background Adherence and persistence to long-term therapy with nucleos(t)ides analogues are crucial to the outcome of treatment in chronic hepatitis B. Our aim was to determine the persistence and adherence rates to nucleos(t)ides analogues in chronic hepatitis B patients under maintenance therapy and to identify relative to prediction of adherence factors. Methods We retrospectively analyzed electronic prescription data of patients (2011–2016; n = 400)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…In the present study, patients receiving ETV showed lower adherence compared with those taking other NUCs. Peng et al 11 , 12 found that those who took LAM or ETV showed lower medication adherence than patients taking telbivudine. Chotiyaputta et al 10 reported that people in receipt of NUCs other than LAM were more likely to have a prevalence of adherence >90%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, patients receiving ETV showed lower adherence compared with those taking other NUCs. Peng et al 11 , 12 found that those who took LAM or ETV showed lower medication adherence than patients taking telbivudine. Chotiyaputta et al 10 reported that people in receipt of NUCs other than LAM were more likely to have a prevalence of adherence >90%.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several studies have reported adherence to antiviral treatment in patients with chronic hepatitis B (CHB), [7][8][9][10][11][12][13][14] and the mean prevalence of adherence to various NUCs ranged from 53.6 to 99%. [8][9][10][11][12] Four studies reported the mean prevalence of adherence to various NUCs of 100%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity-based approach to measuring nucleotide analogs in clinical samples presented here could be extended to detect other drugs used in infectious and non-communicable disease management. Nucleotide analogs and polymerase inhibitors are used to treat hepatitis B, 40 herpes, 41 tuberculosis, 42 and cancer. 43,44 Assays like RESTRICT could support therapeutic monitoring and precision dosing of nucleotide analogs for a variety of diseases to ensure efficacy and safety.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, the overall adherence rate reported herein is relatively high (mean 87.8% and median 92.9%), a finding reported consistently by studies of CHB. [15][16][17][18][19]23,[31][32][33][34] About 61.7% of all patients showed an adherence rate of ≥90%, while only 18.6% showed an adherence rate of <80%. Because antiviral therapy for CHB comprises a single daily dosing of a NUC analogue, which is usually well tolerated with minimal side effects, one can speculate that adherence would be high.…”
Section: Discussionmentioning
confidence: 99%